Effect of freeze-drying on the beta-carotene content of guacamole (@limentech, Ciencia y Tecnología Alimentaria, 2019)
The objective of this research was to study the effect of freeze-drying on the preservation of beta-carotenes present in guacamole. For this purpose, the amount of beta-carotenes contained in the guacamole was determined by spectrophotometry, the color was measured with a spectrophotocolorimeter, then the guacamole was freeze-dried at a freezing temperature of -25º C for 24 hours and finally its effect on the beta-carotene content was analyzed. The results obtained were analyzed with the statistical package SPSS version 13.0, performing analysis of variance (ANOVA), with a degree of significance of 0.05. It was concluded that freeze-drying is a good preservation alternative for guacamole since it preserves the characteristics of the product, retaining a high percentage of beta-carotene content (78%), increases brightness by 121% (no browning) and color purity (greater vividness), preserves the characteristic tone of guacamole.
Keywords: Avocado; Beta-carotenes; Freezing; Guacamole; Lyophilization